Problematic sovereignty : contested rules and political possibilities - Krasner, Stephen D., 1942- (Columbia University Press, 2001)
-- Daniel Deudney, Johns Hopkins University, coeditor of Contested Grounds: Security and Conflict in the New Environmental Politics.